Head injury mechanisms of the occupant under high-speed train rear-end collision - Zhenhao Yu; Lin Jing (Theoretical and Applied Mechanics Letters)
To improve the passive safety of high-speed trains, it is very important to understand the mechanism of head injury in high-speed train collisions. In this study, the head injury mechanisms of occupants in high-speed train rear-end collisions were investigated based on the occupant-seat coupling model, which included a dummy representing the Chinese 50th percentile adult male. The typical injury responses in terms of skull fractures, brain contusions, and diffuse axonal injury (DAI) were analyzed. Meanwhile, the influences of collision speed and seat parameters on head injury response were examined. The simulation results indicate that the skull fractures primarily occur at the skull base region due to excessive neck extension, while the brain contusions and DAI result from the relative displacement of different brain regions. The increase in collision speed will promote the probability of skull fracture, brain contusion, and DAI. Seat design modifications, such as reduced seat spacing, increased seat backrest angles, and selecting the appropriate cushion angle (76°) and friction coefficient (0.15), can effectively mitigate probably occupant's head injury.